An Exploration of Legislative-Executive Conflicts from the Perspective of Human Relations in Nigeria - Egwu, Emmanuel Makoji; Alabi, John O.; Sule, Ja’afaru Garba (International Journal of Social and Administrative Sciences, 2020)
This study focused on the legislative-executive conflicts from the perspective of human relations in Nigeria. The study examined the significant effects of executive-legislature relations and conflicts on the perceived socio-political development of Kogi and Lagos States. Survey research design was adopted. The data gathered were analyzed using both descriptive and inferential analytical techniques. Multiple regression analysis using the ordinary least square (OLS) approach was used for analysis. Findings revealed that struggle for political power, disagreement on budget & financial matters, polarized relationship, legislative arrogance & gridlocks on policies of government have strong significant effects on the perceived socio-political development of Kogi and Lagos States. Furthermore, findings show that struggle for political power & domination, processes re-engineering, pride & personality clash and oversight function of the legislature have effects on the perceived socio-political development of Kogi and Lagos States. The study concluded that management of the legislature-executive relations and conflicts in the Nigerian presidential democracy is vital to socio-political development process of the nation. The study recommended that the executive and the legislature arms should consistently take into account “struggle for political power, disagreement on budget & financial matters, polarized relationship, legislative arrogance & gridlocks on policies of government” as they do not only pattern executive-legislature relationship but also predict the possibility of improved socio-political development of Kogi and Lagos States.